Exclusive breastfeeding counseling and free health checks as efforts to improve community healthy awareness - Azhari; Maulida, Dara; Angkat, Firda Amalia (Talenta Publisher, 2019)
The success of exclusive breastfeeding is a high level of maternal education, a fairly high level of maternal knowledge, the existence of support and understanding of husbands to breastfeed exclusively, the role of potential groups to provide information to pregnant and breastfeeding mothers, the existence of counseling, supportive attitudes of officers and want to respond to every problem that is being faced. From the results of the study it is recommended to maintain and even increase and promote the success of exclusive breastfeeding. ASI is a fat emulsion in a solution of protein, lactose and organic salts that are secreted by the two glands of the mother's breast as the main and best food for infants because in the milk it contains immune, anti-infectious and nutritional nutrients needed to grow and develop and control excess weight gain. body or obesity. Exclusive breast milk is breast milk that is given to infants without additional food at least until the age of 4-6 months